Trajectories of early childhood family instability and the development of externalizing behaviors from middle childhood to adolescence: A prospective study of at‐risk families. Issue 3 (5th January 2022) - Womack, Sean R.; Wilson, Melvin N.; Tong, Xin; Lemery‐Chalfant, Kathryn; Shaw, Daniel S.
Abstract: This study examined associations between trajectories of family instability across early childhood and trajectories of externalizing behaviors from middle childhood to adolescence. Growth mixture models were fit to annual caregiver reports of instability from child ages 2–5 ( N = 731; 49% girls, 50% White). A curve of factors model was fit to externalizing behaviors from child ages 7.5–14. Chronic, elevated instability across early childhood predicted elevated externalizing behaviors from middle childhood to adolescence. Data collection spanned from 2002 to 2017. Increasing or declining levels of instability predicted elevated externalizing behaviors in middle to late childhood, but not in adolescence. Caregiver depressive symptoms mediated the association between instability and the externalizing behavior intercept. Intervening on chronic instability may reduce child externalizing problems.